A feeling of wrongness : pessimistic rhetoric on the fringes of popular culture - Packer, Joseph, 1983-; Stoneman, Ethan (The Pennsylvania State University Press, 2018)
"Examines case studies of popular culture as pessimistic rhetorical artifacts, and how non-traditional modes of argumentation can work rhetorically to overcome biases against pessimistic messaging"--Provided by publisher